Cerium-based abrasive, polishing liquid, method for producing polishing liquid, and method for polishing glass
By using mixed rare earth abrasive particles with high oxidation saw equivalent content in cerium-based abrasives, controlling the dissolution amount of actinium and adding lanthanum dissolution inhibitors, the skin roughness and skin inflammation during the use of abrasives are solved, and the processing performance and grinding speed of the abrasives are improved.
Patent Information
- Application Number
- JP2024510220
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-07-12
- Filing Date
- 2023-07-10
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2043-07-10
AI Technical Summary
The existing cerium-based abrasives are prone to cause rough skin and skin inflammation when used, and the abrasives are not well treated.
The lanthanum dissolution inhibitor is used to reduce skin irritation and inflammation by adding mixed rare earth particles containing 55.0% or more of the oxidation saw (CeO2) equivalent content of rare earth elements to the cerium-based abrasive and controlling the dissolution amount of actinium (La) in the mixture to 40 mg/L or less in the abrasive.
It effectively reduces the rough skin and skin inflammation during the use of cerium-based abrasives, and improves the processing performance and grinding speed of the abrasives.
Smart Images

Figure 0007670231000001 
Figure 0007670231000002 
Figure 0007670231000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a cerium-based abrasive, a polishing liquid, a method for producing the polishing liquid, and a method for polishing glass, which are used for polishing glass materials such as glass substrates used in liquid crystal panels, hard disks, and filters for cutting specific frequencies, and glass substrates for optical lenses. [Background technology]
[0002] Glass materials are used in a variety of applications, and surface polishing may be required depending on the application. In particular, glass materials such as glass substrates used in liquid crystal panels, hard disks, specific frequency cut filters, and glass substrates for optical lenses require highly smooth and efficient surface polishing.
[0003] In the surface polishing of glass materials, which require such excellent polishing performance, cerium-based abrasives as described in Patent Documents 1 and 2, for example, are widely used. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2005 / 042661 [Patent Document 2] International Publication No. 2002 / 031079 Summary of the Invention [Problem to be solved by the invention]
[0005] Cerium-based abrasives are generally used as glass abrasives, and those containing lanthanum are often used. Cerium-based abrasives are generally used in the form of a slurry dispersed in water. The slurry is neutral to alkaline, and depending on the user, it can irritate the skin, causing problems such as rough skin and dermatitis. Therefore, there has been a demand for a cerium-based abrasive that is easier to handle and causes less skin irritation.
[0006] The present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide a cerium-based abrasive, a polishing liquid, a method for producing a polishing liquid, and a method for polishing glass, which are capable of suppressing the occurrence of rough skin and dermatitis. [Means for solving the problem]
[0007] The present invention is based on the discovery that in a cerium abrasive containing mixed rare earth abrasive particles containing lanthanum and cerium, the content of cerium in terms of oxide in the total rare earth element content in terms of oxide (TREO) is 55.0 mass% or more, and the amount of lanthanum dissolved in a mixed liquid containing the cerium-based abrasive and obtained by a specified method is 40 mg / L or less, thereby reducing rough skin and dermatitis that occur when the mixed liquid adheres to the skin.
[0008] That is, the present invention provides the following [1] to
[16] . [1] A cerium-based abrasive containing mixed rare earth abrasive particles containing lanthanum and cerium, The content of the cerium in terms of oxide in the total rare earth element content in terms of oxide (TREO) is 55.0 mass% or more, A 100 mL polyethylene container is charged with 10 g of the cerium-based abrasive, 40 g of pure water, and 130 g of zirconia beads having a particle size of 1 mm. The cerium-based abrasive is pulverized using a ball mill stand at a container rotation speed of 210 rpm for 30 minutes to obtain a mixed solution having a dissolved amount of lanthanum of 40 mg / L or less. [2] The cerium-based abrasive according to [1] above, further comprising a lanthanum dissolution inhibitor. [3] A first agent containing the mixed rare earth abrasive particles; A second agent containing a lanthanum dissolution inhibitor; The cerium-based abrasive according to the above [1], which is a two-component type containing [4] The cerium-based abrasive according to the above [1], which contains 0.1 to 10 mass % of fluorine atoms. [5] The cerium-based abrasive according to the above [1], wherein the content of the lanthanum in the TREO in terms of oxide is 0.01 to 45.0 mass %. [6] The cerium-based abrasive according to [2] or [3] above, wherein the lanthanum dissolution inhibitor is one or more selected from the group consisting of alkali metal carbonates, alkali metal phosphates, alkali metal hydroxides, alkali metal sulfates, alkali metal nitrates, alkali metal organic acid salts, alkaline earth metal carbonates, alkaline earth metal phosphates, alkaline earth metal hydroxides, alkaline earth metal sulfates, alkaline earth metal nitrates, alkaline earth metal organic acid salts, ammonium carbonates, ammonium phosphates, ammonium hydroxides, ammonium sulfates, ammonium nitrates, and ammonium organic acid salts. [7] The cerium-based abrasive according to [6] above, wherein the lanthanum dissolution inhibitor is one or more selected from the group consisting of alkaline earth metal carbonates, alkaline earth metal phosphates, alkaline earth metal organic acid salts, and alkali metal carbonates. [8] The cerium-based abrasive according to [2] or [3] above, wherein the molecular weight of the lanthanum dissolution inhibitor is 300 or less. [9] The cerium-based abrasive according to the above [2] or [3], comprising 0.001 to 0.9 parts by mass of the lanthanum dissolution inhibitor per 100 parts by mass of the mixed rare earth abrasive particles.
[10] A polishing liquid comprising the cerium-based abrasive described in [1] above and at least one selected from water and water-soluble organic solvents.
[11] A method for producing the polishing liquid according to
[10] above, The cerium-based abrasive; one or more selected from the group consisting of water and the water-soluble organic solvent; and mixing the above to form a slurry.
[12] The method for producing a polishing liquid according to
[11] above, wherein the cerium-based abrasive contains the lanthanum dissolution inhibitor.
[13] A method for producing the polishing liquid according to
[10] above, The cerium-based abrasive; The lanthanum dissolution inhibitor; one or more selected from the group consisting of water and the water-soluble organic solvent; and (II) mixing the above to form a slurry.
[14] A method for producing the polishing liquid according to
[10] above, The cerium-based abrasive; one or more selected from the group consisting of water and the water-soluble organic solvent; (III) mixing the above to form a slurry; The slurry obtained in the step (III) is A method for producing a polishing liquid, comprising the step (IV) of adding and mixing the lanthanum dissolution inhibitor.
[15] The method for producing a polishing liquid according to
[14] above, wherein the cerium-based abrasive does not contain the dissolution inhibitor.
[16] A method for polishing glass, comprising the step of using the polishing liquid described in
[10] above. Effect of the Invention
[0009] According to the present invention, it is possible to provide a cerium-based abrasive, a polishing liquid, a method for producing a polishing liquid, and a method for polishing glass, which are capable of suppressing the occurrence of rough skin and dermatitis. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, embodiments of the cerium-based abrasive, the polishing liquid, the method for producing the polishing liquid, and the method for polishing glass of the present invention will be described in detail. In this specification, the terms "50% particle size in the cumulative particle size distribution on a volume basis" and "D 50 " is the particle size at 50% in the cumulative particle size distribution on a volume basis, determined from the particle size distribution measured by a laser diffraction / scattering method. Specifically, it is the value measured using a Microtrack particle size distribution meter described in the Examples below.
[0011] [Cerium-based abrasives] The cerium-based abrasive of this embodiment is a cerium-based abrasive containing mixed rare earth abrasive particles containing lanthanum and cerium, and the content of the cerium in terms of oxide (CeO2) in the total rare earth element content in terms of oxide (TREO; abbreviation for Total Rare Earth Oxides) (hereinafter referred to as "CeO2 amount / TREO") is 55.0 mass% or more. Then, 10 g of the cerium-based abrasive and 40 g of pure water were placed in a 100 mL polyethylene container, along with 130 g of zirconia beads with a particle size of 1 mm. The cerium-based abrasive was pulverized using a ball mill stand at a container rotation speed of 210 rpm for 30 minutes, resulting in a mixed liquid in which the amount of lanthanum dissolved was 40 mg / L or less.
[0012] The TREO in the cerium-based abrasive of this embodiment is derived from mixed rare earth abrasive particles. From the viewpoint of improving the polishing rate, the TREO in the mixed rare earth abrasive particles is preferably 85.0 mass% or more, more preferably 90.0 mass% or more, and even more preferably 92.0 mass% or more; from the viewpoint of containing elements other than the elements constituting TREO to further improve the polishing rate and to suppress the occurrence of surface defects on the polished surface, the TREO content is preferably 99.0 mass% or less, more preferably 98.0 mass% or less, and even more preferably 95.0 mass% or less.
[0013] The content of cerium in TREO calculated as cerium oxide (CeO2) (CeO2 amount / TREO) is 55.0 mass% or more, and from the viewpoint of improving the polishing rate, it is preferably 60.0 mass% or more, more preferably 62.0 mass% or more, and even more preferably 64.0 mass% or more. Moreover, from the viewpoint of ensuring the content of rare earth elements other than Ce and suppressing the occurrence of surface defects on the polished surface, the CeO2 amount / TREO is preferably 90.0 mass% or less, more preferably 80.0 mass% or less, even more preferably 75.0 mass% or less, and even more preferably 70.0 mass% or less.
[0014] The content of the lanthanum oxide (La2O3) in TREO (hereinafter referred to as La2O3 amount / TREO) is preferably 0.01 mass% or more, more preferably 1.0 mass% or more, even more preferably 10.0 mass% or more, even more preferably 20.0 mass% or more, and even more preferably 30.0 mass% or more, from the viewpoint of suppressing the occurrence of scratches on the polished surface. Since the Ce amount in TREO is 55.0 mass% or more, the La2O3 amount / TREO is 45.0 mass% or less, and from the viewpoint of improving the polishing rate and further reducing rough skin and dermatitis, it is preferably 40.0 mass% or less, more preferably 37.0 mass% or less, and even more preferably 35.0 mass% or less.
[0015] The TREO can be measured by oxalate precipitation, calcination and gravimetric methods, specifically, by the method described in the examples below. In addition, the content of each rare earth element such as Ce or La can be measured by instrumental analysis such as high-frequency inductively coupled plasma (ICP) analysis or X-ray fluorescence analysis. In this embodiment, the oxide equivalent amount is the value obtained by converting each rare earth element into its oxide from the measured value obtained by ICP atomic emission spectrometry (ICP-AES).
[0016] The reason why the cerium-based abrasive of the present embodiment can suppress rough skin and dermatitis is not clear, but is thought to be as follows. Lanthanum contained in cerium-based abrasives is dissolved as lanthanum ions in water or water-soluble organic solvents during the manufacture of cerium-based abrasives or when they are made into a slurry. If there is a large amount of dissolved lanthanum in the liquid, it will combine with chloride ions derived from the raw materials of the cerium-based abrasive to produce highly toxic lanthanum chloride, which will adhere to human skin and cause rough skin and dermatitis. On the other hand, by keeping the amount of dissolved lanthanum at a low concentration of 40 mg / L or less, the production of lanthanum chloride and the like is suppressed, and as a result, it is thought that the occurrence of rough skin and dermatitis is suppressed.
[0017] The amount of lanthanum dissolved in the mixed solution obtained by the above-mentioned specified method is 40mg / L or less, and from the viewpoint of suppressing the occurrence of rough skin and dermatitis, it is preferably 35mg / L or less, more preferably 30mg / L or less, and even more preferably 25mg / L or less, and from the viewpoint of cost, it is preferably 0.1mg / L or more, more preferably 0.5mg / L or more, and even more preferably 1.0mg / L or more.When the cerium-based abrasive of this embodiment is used in a slurry state in an actual machine, the ratio of the cerium-based abrasive to the water and water-soluble organic solvent as a dispersion medium in the slurry may be different from that in the above-mentioned specified method, but as long as it is below the lanthanum dissolved concentration measured by this measurement method, the effect of this embodiment is manifested. In this specification, the "amount of dissolved lanthanum" is a value calculated from ICP analysis, specifically, a value calculated by the method described in the Examples below.
[0018] During the production of a cerium-based abrasive or when it is made into a slurry, chloride ions derived from the raw materials of the cerium-based abrasive dissolve in water, a water-soluble organic solvent, or the like together with lanthanum ions. The amount of dissolved chlorine in the mixed solution obtained by the above-mentioned specified method is preferably 40 mg / L or less, more preferably 35 mg / L or less, and even more preferably 25 mg / L or less from the viewpoint of further suppressing the occurrence of rough skin and dermatitis, and is preferably 0.1 mg / L or more, more preferably 0.5 mg / L or more, and even more preferably 1.0 mg / L or more from the viewpoint of cost. In this specification, the "amount of dissolved chlorine" is a value calculated from IC analysis, specifically, a value calculated by the method described in the following examples.
[0019] The particle size (D 50 From the viewpoint of producing the cerium-based abrasive with good productivity, the particle size is preferably 0.10 μm or more, more preferably 0.3 μm or more, even more preferably 0.5 μm or more, and even more preferably 0.7 μm or more. From the viewpoint of obtaining excellent polishing performance capable of reducing polishing scratches and satisfactorily smoothing the polished surface, D 50is preferably 10.0 μm or less, more preferably 5.0 μm or less, and further preferably 3.0 μm or less.
[0020] The specific surface area of the cerium-based abrasive of the present embodiment is preferably 1.0 m2 from the viewpoint of suppressing the occurrence of scratches on the polished surface. 2 / g or more, more preferably 2.0m 2 / g or more, more preferably 3.0m 2 / g or more, and from the viewpoint of improving the polishing rate, it is preferably 10.0 m 2 / g or less, more preferably 8.0m 2 / g or less, more preferably 7.0m 2 / g or less, even more preferably 6.0m 2 / g or less. In this specification, the specific surface area is a value measured by the BET method (single point method).
[0021] The cerium-based abrasive of this embodiment may contain fluorine atoms from the viewpoint of improving the polishing rate. When the cerium-based abrasive contains fluorine atoms, the fluorine atom content in the cerium-based abrasive is preferably 0.1 mass% or more, more preferably 1.0 mass% or more, and even more preferably 3.0 mass% or more from the viewpoint of improving the polishing rate, and is preferably 10.0 mass% or less, more preferably 9.0 mass% or less, even more preferably 8.0 mass% or less, and even more preferably 7.0 mass% or less from the viewpoint of suppressing the occurrence of scratches on the polished surface. The fluorine atom content in the cerium-based abrasive can be measured by melting the cerium-based abrasive in an alkali to prepare an aqueous solution, and then subjecting the solution to an ion electrode method.
[0022] From the viewpoint of improving the polishing rate, the TREO in the cerium-based abrasive of this embodiment is preferably 85.0 mass% or more, more preferably 90.0 mass% or more, and even more preferably 92.0 mass% or more, and from the viewpoint of containing elements other than the elements constituting TREO to further improve the polishing rate and to suppress the occurrence of surface defects (fine surface irregularities) on the polished surface, the TREO content is preferably 99.0 mass% or less, more preferably 97.0 mass% or less, and even more preferably 96.0 mass% or less.
[0023] (Mixed rare earth abrasive particles) In the present embodiment, the "mixture" of the mixed rare earth abrasive particles means that it contains a plurality of rare earth elements. The mixed rare earth abrasive particles may contain rare earth elements other than Ce and La (lanthanum). The rare earth elements include, for example, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, etc.
[0024] The particle size (D 50 From the viewpoint of producing the cerium-based abrasive with good productivity, the average particle diameter is preferably 0.10 μm or more, more preferably 0.3 μm or more, even more preferably 0.5 μm or more, and even more preferably 0.7 μm or more, and from the viewpoint of obtaining excellent polishing performance in which polishing scratches can be reduced and the polished surface can be well smoothed, the average particle diameter is preferably 10.0 μm or less, more preferably 5.0 μm or less, and even more preferably 3.0 μm or less.
[0025] The specific surface area of the mixed rare earth abrasive particles of this embodiment is preferably 1.0 m2 from the viewpoint of suppressing the occurrence of scratches on the polished surface. 2 / g or more, more preferably 2.0m 2 / g or more, more preferably 3.0m 2 / g or more, and from the viewpoint of improving the polishing rate, it is preferably 10.0 m 2 / g or less, more preferably 8.0m 2 / g or less, more preferably 7.0m 2 / g or less, even more preferably 6.0m 2 / g or less. In this specification, the specific surface area is a value measured by the BET method (single point method).
[0026] The mixed rare earth abrasive particles of this embodiment may contain fluorine atoms from the viewpoint of improving the polishing rate. When the mixed rare earth abrasive particles contain fluorine atoms, the fluorine atom content in the mixed rare earth abrasive particles is preferably 0.1 mass% or more, more preferably 1.0 mass% or more, and even more preferably 3.0 mass% or more from the viewpoint of improving the polishing rate, and is preferably 10.0 mass% or less, more preferably 9.0 mass% or less, even more preferably 8.0 mass% or less, and even more preferably 7.0 mass% or less from the viewpoint of suppressing the occurrence of scratches on the polished surface.
[0027] (Lanthanum dissolution inhibitor) The cerium-based abrasive of this embodiment may contain, in addition to the mixed rare earth abrasive particles, a lanthanum dissolution inhibitor that inhibits the dissolution of lanthanum. As the lanthanum dissolution inhibitor, a compound having the effect of converting lanthanum ions dissolved in water or a water-soluble organic solvent, etc., into an insoluble salt, etc., and precipitating the salt, or a compound having the effect of immobilizing lanthanum ions by a chelating action, is preferred. Such a lanthanum dissolution inhibitor is preferably at least one selected from alkali metal carbonates, alkali metal phosphates, alkali metal hydroxides, alkali metal sulfates, alkali metal nitrates, alkali metal organic acid salts, alkaline earth metal carbonates, alkaline earth metal phosphates, alkaline earth metal hydroxides, alkaline earth metal sulfates, alkaline earth metal nitrates, alkaline earth metal organic acid salts, ammonium carbonates, ammonium phosphates, ammonium hydroxides, ammonium sulfates, ammonium nitrates, and ammonium organic acid salts, and from the viewpoint of the safety of the salts produced, more preferably at least one selected from alkaline earth metal carbonates, alkaline earth metal phosphates, alkaline earth metal organic acid salts, and alkali metal carbonates.
[0028] As the alkali metal, from the viewpoint of the safety of the salt to be produced, sodium and potassium are preferred, and sodium is more preferred. From the same viewpoint, calcium and magnesium are preferred as the alkaline earth metal. Specific examples of preferred lanthanum dissolution inhibitors include monocalcium phosphate, dicalcium phosphate, calcium hydroxide, calcium carbonate, calcium gluconate, calcium citrate, sodium bicarbonate, ammonium bicarbonate, dimagnesium phosphate, dicalcium phosphate, and the like. Of these, dicalcium phosphate is more preferred from the viewpoints of further suppressing the occurrence of rough skin and dermatitis, the safety of the salt produced, and suppressing the occurrence of scratches on the polishing surface. The lanthanum dissolution inhibitors may be used alone or in combination of two or more.
[0029] From the viewpoint of further suppressing the occurrence of rough skin and dermatitis, the molecular weight of the lanthanum dissolution inhibitor is preferably at least 50, more preferably at least 75, even more preferably at least 100, and is preferably at most 300, more preferably at most 200, even more preferably at most 150. A molecular weight of 300 or less is preferred because it has high reactivity with lanthanum ions and a high lanthanum dissolution suppression effect.
[0030] When the cerium-based abrasive of this embodiment contains a lanthanum dissolution inhibitor, the cerium-based abrasive may be a one-component type that already contains the lanthanum dissolution inhibitor, or it may be a two-component type that contains a first component containing the mixed rare earth abrasive particles and a second component containing the lanthanum dissolution inhibitor.
[0031] When the cerium-based abrasive is a two-component type containing a first agent containing the mixed rare earth abrasive particles and a second agent containing a lanthanum dissolution inhibitor, etc., the content of the mixed rare earth abrasive particles in the first agent is preferably 85.0 mass% or more, more preferably 90.0 mass% or more, and even more preferably 92.0 mass% or more from the viewpoint of improving the polishing rate, and is preferably 99.9 mass% or less, more preferably 99.5 mass% or less, and even more preferably 99.2 mass% or less from the viewpoint of suppressing the occurrence of rough skin and dermatitis.
[0032] The content of the lanthanum dissolution inhibitor in the cerium-based abrasive, in both the single-component type and the double-component type, is preferably 0.95 parts by mass or less, more preferably 0.85 parts by mass or less, and even more preferably 0.75 parts by mass or less, based on 100 parts by mass of mixed rare earth abrasive particles, from the viewpoint of cost.Furthermore, from the viewpoint of suppressing the occurrence of rough skin and dermatitis, it is preferably 0.001 parts by mass or more, more preferably 0.01 parts by mass or more, and even more preferably 0.1 parts by mass or more. In addition, the content of the lanthanum dissolution inhibitor in the cerium-based abrasive is preferably 0.95% by mass or less, more preferably 0.90% by mass or less, even more preferably 0.80% by mass or less, and even more preferably 0.70% by mass or less, in terms of cost, in both the one-component type and two-component type. In addition, in terms of suppressing the occurrence of rough skin and dermatitis, it is preferably 0.001% by mass or more, more preferably 0.01% by mass or more, even more preferably 0.05% by mass or more, and even more preferably 0.1% by mass or more. It is.
[0033] (Additives) In order to improve dispersibility, prevent sedimentation, prevent solidification, improve stability and improve workability, the cerium-based abrasive of this embodiment may be added with additives such as glycols such as ethylene glycol and polyethylene glycol, polymer dispersants such as sodium salt of polyacrylic acid, polycarboxylic acid polymers, polysulfonic acid polymers, cellulose ethers such as methyl cellulose and carboxymethyl cellulose, water-soluble polymers such as polyvinyl alcohol, phosphoric acid compounds, etc. These may be used alone or in combination of two or more. When additives are added, among these, polymer dispersants, phosphoric acid compounds, and cellulose ethers are preferred from the viewpoint of improving dispersibility, preventing sedimentation, preventing solidification, improving stability and improving workability. Examples of polymer dispersants include poly(meth)acrylic acid, polyhydroxy(meth)acrylic acid, (meth)acrylic acid copolymers such as copolymers of (meth)acrylic acid and maleic acid, copolymers of olefin and maleic acid, copolymers of maleic acid and alkylene oxide adducts such as ethylene oxide or propylene oxide of allyl alcohol, copolymers of allylsulfonic acid and maleic acid, etc., or alkali metal salts such as sodium salts and potassium salts thereof. Among these, polyacrylic acid, copolymers of acrylic acid and maleic acid, or alkali metal salts thereof are preferred, copolymers of acrylic acid and maleic acid or alkali metal salts thereof are more preferred, and sodium salts of copolymers of acrylic acid and maleic acid are even more preferred. Examples of phosphoric acid compounds include inorganic phosphoric acids such as tripolyphosphoric acid, pyrophosphoric acid, tetrametaphosphoric acid, hexametaphosphoric acid, orthophosphoric acid, and phosphorous acid; organic phosphonic acids such as aminotrimethylenephosphonic acid, 1-hydroxyethylidene-1,1-diphosphonic acid, ethylenediaminetetramethylenephosphonic acid, and diethylenetriaminepentamethylenephosphonic acid; and alkali metal salts thereof such as sodium salts and potassium salts. Among these, tripolyphosphoric acid, pyrophosphoric acid, hexametaphosphoric acid, and alkali metal salts thereof are preferred, and sodium tripolyphosphate is more preferred.
[0034] When the cerium-based abrasive contains an additive, the content of the additive per 100 parts by mass of the mixed rare earth abrasive particles is, from the standpoints of improving dispersibility, preventing sedimentation, preventing solidification, improving stability, and improving workability, preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, even more preferably 0.3 parts by mass or more, and even more preferably 0.5 parts by mass or more, and from the standpoint of cost, is preferably 10.0 parts by mass or less, more preferably 5.0 parts by mass or less, and even more preferably 3.0 parts by mass or less. Furthermore, when the cerium-based abrasive contains an additive, the content of the additive in the cerium-based abrasive is preferably 0.01 mass % or more, more preferably 0.1 mass % or more, even more preferably 0.3 mass % or more, and still more preferably 0.5 mass % or more, from the viewpoint of improving dispersibility, preventing sedimentation, preventing solidification, improving stability, and improving workability, and is preferably 10.0 mass % or less, more preferably 5.0 mass % or less, and even more preferably 3.0 mass % or less, from the viewpoint of cost.
[0035] [Method of manufacturing cerium-based abrasives] The method for producing a cerium-based abrasive is not particularly limited, but specifically, it is preferable to produce a cerium-based abrasive through the steps of (1) preparing a mixed light rare earth compound, (2) producing a mixed rare earth oxide raw material from the mixed light rare earth compound, and (3) wet-grinding the mixed rare earth oxide raw material, followed by calcination, crushing and classification to obtain mixed rare earth abrasive particles. In addition, from the viewpoint of further suppressing the occurrence of rough skin and dermatitis, it is more preferable to produce a cerium-based abrasive through the steps of (4) adding and mixing a lanthanum dissolution inhibitor after the step (3) or preparing a second agent containing a lanthanum dissolution inhibitor. The "mixing" referred to here is also synonymous with the "mixing" of the above-mentioned mixed rare earth abrasive particles. Each step will be described in order below.
[0036] (Process (1)) In step (1), a mixed light rare earth compound is prepared. The method for preparing the mixed light rare earth compound is not particularly limited. The mixed light rare earth compound can be obtained, for example, by separating and reducing impurities other than rare earth elements and medium and heavy rare earths from ore containing rare earth elements by chemical treatment. As the mixed light rare earth compound, it is preferable that the content of non-rare earth impurities such as alkali metals, alkaline earth metals, and radioactive substances, as well as the content of medium and heavy rare earths is reduced. In this specification, medium and heavy rare earths refer to rare earth elements having atomic numbers greater than Pm, and rare earth elements other than medium and heavy rare earths are referred to as light rare earths. As the ore containing rare earth elements, for example, rare earth concentrates obtained from raw material ores such as natural monazite and bastnaesite, which contain a large amount of Ce, are suitably used.
[0037] In the preparation of the mixed light rare earth compound, roasting with sulfuric acid is a common chemical treatment method for reducing the content of impurities. In the roasting with sulfuric acid, the crushed raw ore is roasted with sulfuric acid to generate sulfates (rare earth sulfates), which are dissolved in water to obtain a rare earth sulfate solution, and the impurities, which are insoluble, are removed by filtration or the like. The content of impurities in the mixed light rare earth compound is preferably reduced to 1.0 mass% or less. In addition, a chemical treatment method for reducing the content of medium and heavy rare earths can be carried out, for example, by adding carbonate to the rare earth sulfate solution after the sulfuric acid roasting to obtain crude rare earth carbonate, adding hydrochloric acid to the crude rare earth carbonate to obtain a mixed rare earth chloride aqueous solution, and then performing solvent extraction using an organic solvent. In the solvent extraction, the contents of cerium, lanthanum, and other light rare earths can be adjusted as necessary using known methods such as adjusting the degree of extraction or using additives. The content of medium and heavy rare earths in the mixed light rare earth compound is preferably reduced to 1.0 mass% or less.
[0038] (Process (2)) In step (2), a mixed rare earth oxide raw material is produced from the mixed light rare earth compound. The method for producing the mixed rare earth oxide raw material from the mixed light rare earth compound is not particularly limited. The mixed rare earth oxide raw material can be obtained, for example, by producing a mixed rare earth carbonate, which is a carbonate, using the mixed light rare earth compound and sodium carbonate, ammonium bicarbonate, or the like, and calcining the mixed rare earth carbonate. The firing temperature when the mixed rare earth carbonate is fired to obtain a mixed rare earth oxide raw material is appropriately adjusted depending on the composition of the mixed rare earth carbonate, but is preferably 500 to 1200° C., more preferably 600 to 1100° C., and even more preferably 700 to 1000° C. The firing time is preferably 0.5 to 48 hours, more preferably 1 to 40 hours, and even more preferably 1.5 to 30 hours. The firing atmosphere is preferably air. After firing, the mixed rare earth oxide raw material may be crushed by a mechanical method to adjust the particle size to a desired size.
[0039] The mixed rare earth oxide raw material is commercially available, and a commercially available product may be used. The mixed rare earth oxide raw material can be obtained by calcining a mixed light rare earth compound such as a mixed rare earth carbonate, a mixed rare earth monooxycarbonate, a mixed rare earth oxalate, or a mixed rare earth hydroxide, and therefore the mixed rare earth carbonate, mixed rare earth monooxycarbonate, mixed rare earth oxalate, or the like, which are the raw materials used for producing the mixed rare earth oxide raw material, may remain in the commercially available mixed rare earth oxide raw material.
[0040] (Step (3)) In step (3), the mixed rare earth oxide raw material is wet-pulverized, then calcined, crushed and classified to obtain mixed rare earth abrasive particles. From the viewpoint of obtaining homogeneous mixed rare earth abrasive particles, the wet grinding is preferably carried out using a media mill such as a wet ball mill. As the dispersion medium, water, a water-soluble organic solvent, etc. are preferably used. After the wet grinding, the mixture is dried, calcined, crushed, and classified to obtain mixed rare earth abrasive particles. The drying, calcination, crushing and classification can be carried out in the same manner as in the conventional production of mixed rare earth abrasive particles.
[0041] From the viewpoint of sufficiently reacting the raw material to be fired by firing, the firing temperature is preferably 600 to 1200° C., more preferably 650 to 1150° C., and even more preferably 700 to 1100° C. The firing time at the target temperature is preferably 0.1 to 10 hours, more preferably 0.5 to 6 hours, and even more preferably 0.5 to 4 hours. The firing atmosphere is preferably air.
[0042] From the viewpoint of improving polishing speed, the mixed rare earth abrasive particles may contain fluorine atoms.In this case, the method of containing fluorine atoms is not particularly limited, but the method of mixing the mixed rare earth oxide raw material with the mixed rare earth fluoride raw material, wet grinding, calcining, crushing and classifying to obtain the mixed rare earth abrasive particles is preferred.
[0043] The method for obtaining the mixed rare earth fluoride raw material is not particularly limited, but for example, it can be obtained by adding a fluoride such as hydrofluoric acid, ammonium fluoride or acidic ammonium fluoride as a fluorine source to the mixed light rare earth compound and performing heat treatment. From the viewpoint of obtaining a cerium-based abrasive that is homogeneous and has excellent polishing properties, the heat treatment is preferably performed at 400° C. or less. The heat treatment atmosphere is preferably air. The heat treatment time is preferably 0.1 to 10 hours, more preferably 0.5 to 5 hours, and even more preferably 1.0 to 4 hours. The firing atmosphere is preferably air. The method of obtaining mixed rare earth abrasive particles by mixing a mixed rare earth oxide raw material with a mixed rare earth fluoride raw material is safer and less costly than the method of obtaining mixed rare earth abrasive particles by directly adding a fluoride such as ammonium fluoride or hydrofluoric acid to a mixed rare earth oxide raw material, and makes it easy to obtain mixed rare earth abrasive particles containing fluorine.
[0044] The content of TREO in the mixed rare earth fluoride raw material is preferably 75% by mass or more, more preferably 80% by mass or more, and even more preferably 82% by mass or more. The mixed rare earth fluoride raw material is preferably one in which cerium is the main component of all rare earth elements contained therein. The content of cerium in TREO in terms of oxide (CeO2 content / TREO) is preferably 55.0% by mass or more, and from the viewpoint of improving the polishing rate, it is more preferably 60.0% by mass or more, even more preferably 62.0% by mass or more, and even more preferably 64.0% by mass or more. The content of CeO2 / TREO is preferably 90.0% by mass or less, more preferably 80.0% by mass or less, even more preferably 75.0% by mass or less, and even more preferably 70.0% by mass or less, from the viewpoint of ensuring the content of rare earth elements other than Ce and suppressing the occurrence of surface defects on the polished surface.
[0045] The fluorine atom content in the mixed rare earth fluoride raw material is preferably 10 to 30 mass %, more preferably 15 to 30 mass %, and further preferably 20 to 30 mass %. The amount of the mixed rare earth fluoride raw material added to the mixed rare earth oxide raw material is appropriately determined according to the fluorine atom content required for the cerium-based abrasive to be manufactured. From the viewpoint of obtaining excellent polishing properties, the amount of the mixed rare earth fluoride raw material added is preferably 1 to 40 mass%, more preferably 3 to 35 mass%, and further preferably 5 to 30 mass%, relative to 100 mass% in total of the mixed rare earth oxide raw material and the mixed rare earth fluoride raw material.
[0046] (Step (4)) In step (4), after step (3), a lanthanum dissolution inhibitor is added to and mixed with the mixed rare earth abrasive particles obtained in step (3), or a second agent containing a lanthanum dissolution inhibitor is prepared. In this embodiment, when the cerium-based abrasive is a one-component type, the mixed rare earth abrasive particles can be used as the cerium-based abrasive without going through step (4), or the mixed rare earth abrasive particles obtained in step (3) can be mixed with a lanthanum dissolution inhibitor to make a cerium-based abrasive. Also, if necessary, an additive can be mixed with the lanthanum dissolution inhibitor. The mixing method is not particularly limited, and for example, mixing may be performed using a mixer such as a batch mixer, or mixing may be performed using a media mill such as a ball mill or a bead mill. In this embodiment, when the cerium-based abrasive is a two-component type, a second agent containing a lanthanum dissolution inhibitor is prepared in step (4). In this embodiment, when the cerium-based abrasive is a two-component type containing a first agent containing the mixed rare earth abrasive particles and a second agent containing a lanthanum dissolution inhibitor, the first agent containing the mixed rare earth abrasive particles and the second agent containing the lanthanum dissolution inhibitor may be prepared separately, and the first agent and the second agent may be mixed when producing the polishing liquid. The second agent may or may not contain water, a water-soluble organic solvent, additives, and the like in addition to the lanthanum dissolution inhibitor.
[0047] [Polishing liquid] The polishing liquid of this embodiment contains the above-mentioned cerium-based abrasive and one or more selected from water and a water-soluble organic solvent. The polishing liquid preferably contains a lanthanum dissolution inhibitor from the viewpoint of further suppressing the occurrence of rough skin and dermatitis. The polishing liquid may also contain components other than the cerium-based abrasive, one or more selected from water and a water-soluble organic solvent, and the lanthanum dissolution inhibitor. The polishing liquid of the present embodiment is a polishing liquid that suppresses rough skin, dermatitis, and the like that may occur when the polishing liquid adheres to human skin.
[0048] From the viewpoint of achieving good polishing performance and from the viewpoint of cost, the content of the cerium-based abrasive in the polishing liquid is preferably within the range of 0.1 to 40.0 mass%, more preferably 1.0 to 35.0 mass%, even more preferably 3.0 to 30.0 mass%, and even more preferably 5.0 to 20.0 mass%. In addition, when preparing the polishing liquid, additives such as a pH adjuster, an antifoaming agent, and an anti-rust agent may be added as necessary, within the range that does not impair the polishing performance, taking into consideration the object to be polished and the specifications of the polishing apparatus, etc.
[0049] The polishing liquid is particularly suitable for finish polishing of various glass materials and glass products, such as glass substrates for optical disks and magnetic disks, glass substrates for liquid crystal displays, glass substrates for color filters and photomasks, and glass substrates for optical lenses.
[0050] [Method of manufacturing the polishing liquid] The method for producing a polishing liquid of the present invention is a method for producing a polishing liquid containing the above-mentioned cerium-based abrasive and at least one selected from water and a water-soluble organic solvent. In one embodiment of the present invention, the method for producing a polishing liquid includes a step (I) of mixing the cerium-based abrasive with at least one selected from the group consisting of water and the water-soluble organic solvent to form a slurry, in which the cerium-based abrasive may or may not contain the lanthanum dissolution inhibitor.
[0051] In addition, when the cerium-based abrasive is a two-component type containing a first agent containing mixed rare earth abrasive particles and a second agent containing a lanthanum dissolution inhibitor, step (I) is carried out using the first agent and the second agent as the cerium-based abrasive.
[0052] In step (I), the method for forming a slurry is not particularly limited. For example, the slurry may be formed by mixing with a stirrer, or may be formed by using a grinding machine such as a wet ball mill, an attritor, or a bead mill.
[0053] In another embodiment of the present invention, the method for producing a polishing liquid includes a step (II) of mixing the cerium-based abrasive, the lanthanum dissolution inhibitor, and at least one selected from the group consisting of water and the water-soluble organic solvent to form a slurry. In this case, the cerium-based abrasive may or may not contain the lanthanum dissolution inhibitor. The method for forming a slurry in the step (II) is the same as the method for forming a slurry in the above step (I).
[0054] In yet another embodiment of the present invention, the method for producing a polishing liquid includes the steps of: mixing the cerium-based abrasive with at least one selected from the group consisting of water and the water-soluble organic solvent to form a slurry; and adding and mixing the lanthanum dissolution inhibitor into the slurry obtained in the step (III). The cerium-based abrasive may or may not contain the lanthanum dissolution inhibitor. The method for forming a slurry in the step (III) is the same as the method for forming a slurry in the above step (I).
[0055] [Glass polishing method] The method for polishing glass of the present invention is a method for performing polishing using the polishing liquid as described above. The glass polishing method is not particularly limited except for using the polishing liquid, and can be a method using a known polishing device, etc. The polishing liquid can be used by a known method, for example, when performing finish polishing such as mirror polishing of a glass material with a single-sided polisher or a double-sided polisher. EXAMPLES
[0056] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples. In addition, the mixed rare earth oxide raw material, the mixed rare earth fluoride raw material, the TREO in the examples and comparative examples, and the oxide-equivalent content of each rare earth element in the TREO (CeO2 amount / TREO, La2O3 amount / TREO, Nd2O3 amount / TREO, Pr6O 11 The amount of fluorine atom / TREO and the fluorine atom content were calculated as follows. [TREO] Ammonia water was added to the solution in which the measurement sample was dissolved in acid. The resulting precipitate was filtered and washed to remove the alkali metals, and then dissolved in acid again. Oxalic acid was added to this solution, and the resulting precipitate was fired in air at 800°C for 2 hours, and the TREO was determined by gravimetric method. The TREO of mixed rare earth abrasive particles is calculated by "total rare earth oxide mass obtained after firing / mass of mixed rare earth abrasive particles before acid dissolution treatment", and the TREO of cerium abrasive is calculated by "total rare earth oxide mass obtained after firing / mass of cerium abrasive before acid dissolution treatment". [Oxide-equivalent content of each rare earth element in TREO] The measurement sample was dissolved in acid, and the amount of each rare earth element measured by ICP-AES was calculated as an oxide and the value was calculated relative to TREO. [Fluorine atom content] The measurement sample was fused with an alkali, extracted with hot water, and measured with a fluoride ion meter (manufactured by Horiba, Ltd.; ion electrode method).
[0057] [Preparation of mixed rare earth oxide raw materials] (Mixed rare earth oxide raw material A) Raw ore (rare earth concentrate) containing 47% by mass of TREO, 2% by mass of medium and heavy rare earths in oxide equivalent, and 8% by mass of neodymium in oxide equivalent was treated by sulfuric acid calcination method and solvent extraction method to reduce impurities other than rare earth elements to 1% or less and medium and heavy rare earths to 1% or less in oxide equivalent to obtain a mixed light rare earth compound with an adjusted rare earth element content. This mixed light rare earth compound has a cerium oxide equivalent ([CeO2]) content in TREO (CeO2 amount / TREO) of 64.7% by mass, a lanthanum oxide equivalent ([La2O3]) content (La2O3 amount / TREO) of 34.1% by mass, a neodymium oxide equivalent ([Nd2O3]) content (Nd2O3 amount / TREO) of 0.6% by mass, and a praseodymium oxide equivalent ([Pr6O 11 ]) Content (Pr6O 11 The amount of TREO was 0.2 mass%. This mixed light rare earth compound was treated with ammonium bicarbonate to obtain a mixed rare earth carbonate, which had 49% by mass of TREO. This mixed rare earth carbonate was heat-treated in a sintering furnace in the atmosphere at 800°C for 10 hours to obtain a mixed rare earth oxide raw material A. The TREO, CeO2 content / TREO, La2O3 content / TREO, Nd2O3 content / TREO, and Pr6O 11 The amount / TREO is shown in Table 1.
[0058] (Mixed rare earth oxide raw materials B~E) In the same manner as in the preparation of mixed rare earth oxide raw material A, mixed light rare earth compounds were used and the treatment conditions thereof and the heat treatment conditions of the mixed rare earth carbonate were adjusted to prepare mixed rare earth oxide raw materials B to E. The TREO, CeO2 content / TREO, La2O3 content / TREO, Nd2O3 content / TREO, and Pr6O 11 The amount / TREO is shown in Table 1.
[0059] [Table 1]
[0060] [Preparation of mixed rare earth fluoride raw materials] (Mixed rare earth fluoride raw material F) After adding hydrofluoric acid to the mixed light rare earth compound and mixing, the mixture was heat-treated in air at 400°C for 2 hours to obtain mixed fluorinated rare earth material F. Table 2 shows the TREO, CeO2 amount / TREO, and fluorine content of this mixed fluorinated rare earth material F.
[0061] (Mixed rare earth fluoride raw materials G~I) In the same manner as in the preparation of mixed fluorinated rare earth raw material F, mixed light rare earth compounds were used and the treatment conditions were adjusted to prepare mixed fluorinated rare earth raw materials G to I. The TREO, CeO2 amount / TREO, and fluorine content of mixed fluorinated rare earth raw materials G to I are shown in Table 2.
[0062] [Table 2]
[0063] [Manufacturing of cerium-based abrasives] Cerium-based abrasives were produced according to the following examples and comparative examples. Details of the additives used in the following Examples and Comparative Examples are given below. Additive 1: Sodium tripolyphosphate (Kanto Chemical Co., Ltd.): molecular weight over 300 Additive 2: Sodium salt of polyacrylic acid "Poise 530" (Kao Corporation): molecular weight over 300 Additive 3: Sodium salt of copolymer of acrylic acid and maleic acid "Poise 521" (Kao Corporation): molecular weight over 300 Additive 4: Carboxymethylcellulose (Kanto Chemical Co., Ltd.): molecular weight over 300 Additive 5: Crystalline cellulose "Cellulose microcrystal" (Kanto Chemical Co., Ltd.): molecular weight over 300
[0064] Example 1 1000 kg of water and a total of 1400 kg of the mixed rare earth oxide raw material A and the mixed rare earth fluoride raw material F (mass ratio 76:24) were stirred and mixed in a slurry tank, and then mixed and pulverized for 17 hours in a wet ball mill (medium: zirconia balls with a diameter of 5 mm) to obtain a uniform mixed solution. This mixed solution was placed in a rotary kiln, dried in air at 700°C for 1 hour, and then fired at 960°C for 4 hours. The fired body was allowed to cool, then crushed and classified to obtain mixed rare earth abrasive particles. Dicalcium phosphate was added as a lanthanum dissolution inhibitor to the mixed rare earth abrasive particles in an amount of 0.1 parts by mass per 100 parts by mass of the mixed rare earth abrasive particles, and mixed with a stirrer to produce a cerium-based abrasive.
[0065] (Examples 2 to 25 and Comparative Examples 1 to 5) A cerium-based abrasive was produced in the same manner as in Example 1, except that the mixed rare earth oxide raw material, mixed rare earth fluoride raw material, firing temperature, lanthanum dissolution inhibitor, and additives 1 to 5 were as shown in Tables 3 and 4.
[0066] [Measurement of physical properties of mixed rare earth abrasive particles and cerium-based abrasives] The mixed rare earth abrasive and the cerium-based abrasive produced as described above were subjected to the following physical property measurements. The results of these physical property measurements are shown in Tables 3 and 4 below.
[0067] (Particle size distribution D 50 ) Cerium-based abrasive particles or mixed rare earth abrasive particles were dispersed in pure water containing a dispersant to prepare a measurement sample. The particle size distribution of the cerium-based abrasive was measured by the laser diffraction scattering method using a Microtrac particle size distribution analyzer "MT3300II" (manufactured by Nikkiso Co., Ltd.). The particle diameter at 50% cumulative volume (D 50 ) was sought.
[0068] (specific surface area) The specific surface area of cerium-based abrasive particles or mixed rare earth abrasive particles was measured in accordance with "6.2 Fluidized method (3.5) Single point method" of JIS R 1626:1996 (Method of measuring specific surface area of fine ceramic powder by gas adsorption BET method). Nitrogen was used as the adsorbate gas.
[0069] [Evaluation of cerium-based abrasives] The cerium-based abrasives produced in the above Examples and Comparative Examples were evaluated as follows. The evaluation results are summarized in Table 5 below.
[0070] (Dissolved Ion Analysis) When cerium-based abrasive was dispersed in water, the amounts of lanthanum, fluorine, and chlorine dissolved in the water were calculated by ICP analysis and IC analysis. [Preparation of samples for ICP and IC analysis] A 100 mL polyethylene container was charged with 10 g of the cerium-based abrasive and 40 g of pure water as slurry components, as well as 130 g of zirconia beads with a particle size of 1 mm as beads. Using a ball mill stand, the cerium-based abrasive was pulverized for 30 minutes at a container rotation speed of 210 rpm to obtain a mixed solution. 20 mL of the resulting mixed solution was collected and filtered with a membrane filter "SLHN033NS" (manufactured by Nihon Millipore Co., Ltd.) with a mesh size of 0.45 μm, and then further filtered with a membrane filter "VSWP02500" (manufactured by Nihon Millipore Co., Ltd.) with a mesh size of 0.025 μm attached to a syringe holder to prepare an analytical sample. Note that the analytical sample was used within 48 hours after preparation, and ICP and IC analyses were performed.
[0071] [ICP analysis] To 10 mL of the obtained analytical sample, 10 mL of an aqueous solution of nitric acid (concentration 70% by mass) and ultrapure water mixed at a volume ratio of 1:1 was added, and then the volume was increased to 100 mL with ultrapure water to prepare a sample for ICP analysis. The absorbance of this sample for ICP analysis was measured at a wavelength of 333.749 nm using an ICP optical emission spectrometer "iCap7000Duo" (manufactured by Thermo Fisher Scientific Co., Ltd.), and the mass concentration (mg / L) of lanthanum atoms was calculated.
[0072] [IC analysis] The resulting analytical sample (10 mL) was diluted 20 times with ultrapure water to prepare an IC analysis sample. This IC analysis sample was measured using an ion chromatography system "ICS-1600" (manufactured by Thermo Fisher Scientific Co., Ltd.) with an eluent containing sodium carbonate and sodium bicarbonate, and the mass concentrations (mg / L) of fluorine ions and chloride ions were calculated.
[0073] (Evaluation of rough skin and dermatitis) 10g of the cerium-based abrasive obtained in the examples and comparative examples and 40g of pure water were placed in a 100mL polyethylene container, and 130g of zirconia beads with a particle size of 1mm were placed in the container. The cerium-based abrasive was pulverized using a ball mill stand at a container rotation speed of 210rpm for 30 minutes to obtain a mixed solution with a cerium-based abrasive content of 20% by mass. The occurrence of rough skin and dermatitis was examined using this mixed solution. Specifically, 0.2 ml of the abrasive slurry was applied to the gauze of a bandage on five subjects, and after thorough application, the test substance was directly applied to the inside of the forearm of each subject, and the condition of the skin surface was observed after 30 minutes. Based on the fact that itching and erythema are observed as the rough skin and dermatitis progress, if no itching or erythema was observed, it was considered as no change, if there was itching, it was considered as slightly worse, if there was slight erythema, it was considered as worse, and if there was clearly erythema, it was considered as clearly worse. The results were scored according to the following rough skin evaluation criteria. [Criteria for assessing the effect of suppressing rough skin and dermatitis] 0 points: No change 1 point: Slightly worse 2 points: Worsening 3 points: Clearly worsening
[0074] (Polishing evaluation) Using each of the cerium-based abrasives obtained in the above Examples and Comparative Examples, 48 g of the cerium-based abrasive, 272 g of pure water, and a rotor of φ8×40 mm were placed in a 500 ml beaker, and stirred at 500 rpm for 1 hour using a magnetic stirrer REXIM "RS-1DN" manufactured by AS ONE Corporation, to prepare an abrasive slurry containing 15% by mass of the cerium-based abrasive. Using this abrasive slurry, a sample of alkali-free glass for TFT liquid crystal displays (50 mm×50 mm×thickness 1.1 mm, polishing area 25 cm) was polished under the following polishing conditions. 2 ) was polished using a single-sided polisher, and the polishing speed and polishing scratches were evaluated. [Polishing conditions] Polishing pad: suede pad Lower surface plate rotation speed: 260rpm Grinding pressure: 100g / cm 2 Polishing time: 20 minutes x 3 sheets
[0075] The evaluation methods are as follows: [Polishing speed] The thickness of each sample was measured before and after polishing at five points with a micrometer, and the average thickness reduction (ΔT [μm]) was calculated. The average value of [ΔT / polishing time (20 minutes)] for three samples was taken as the polishing rate. [Polishing scratches] After polishing, the polished surface of the sample was observed under a differential interference microscope (Olympus Corporation, "BX51M") at a magnification of 50 times, the number of scratches was counted, and the average value for three samples was calculated.
[0076] [Table 3]
[0077] [Table 4]
[0078] [Table 5]
[0079] As can be seen from Table 5, it was confirmed that the cerium-based abrasives (Examples 1 to 25) in which the amount of lanthanum dissolved in the mixed solution obtained by a predetermined method was 40 mg / L or less suppressed the occurrence of rough skin and dermatitis. It was also confirmed that the polishing solution containing the cerium-based abrasive suppressed the occurrence of polishing scratches and enabled polishing at a good polishing rate.
Claims
1. A cerium-based abrasive containing mixed rare earth abrasive particles containing lanthanum, cerium and fluorine atoms, and a lanthanum dissolution inhibitor, The mixed rare earth abrasive particles have a fluorine atom content of 0.1% by mass or more and 10% by mass or less; The content of cerium in terms of oxide is 55.0 mass% or more and 90.0 mass% or less in terms of oxide, and the content of lanthanum in terms of oxide is 1.0 mass% or more and 45.0 mass% or less in terms of oxide, in the total content of rare earth elements in terms of oxide (TREO), Particle size (D 50 ) is 0.10 μm or more and 10.0 μm or less, Specific surface area is 1.0 m 2 / g or more 10.0m 2 / g or less, the lanthanum dissolution inhibitor is at least one selected from the group consisting of an alkali metal carbonate, an alkaline earth metal carbonate, an alkaline earth metal phosphate, and an alkaline earth metal organic acid salt; The content of the lanthanum dissolution inhibitor is 0.01 parts by mass or more and 1.00 parts by mass or less per 100 parts by mass of the mixed rare earth abrasive particles, A 100 mL polyethylene container is charged with 10 g of the cerium-based abrasive, 40 g of pure water, and 130 g of zirconia beads having a particle size of 1 mm. The cerium-based abrasive is pulverized using a ball mill stand at a container rotation speed of 210 rpm for 30 minutes to obtain a mixed liquid having a dissolved amount of lanthanum of 40 mg / L or less.
2. a first agent containing the mixed rare earth abrasive particles; A second agent containing a lanthanum dissolution inhibitor; 2. The cerium-based abrasive according to claim 1, which is a two-component type comprising:
3. 2. The cerium-based abrasive according to claim 1, wherein the fluorine atom is contained in an amount of 0.1 to 10 mass %.
4. 4. The cerium-based abrasive according to claim 1, wherein the molecular weight of the lanthanum dissolution inhibitor is 300 or less.
5. 4. The cerium-based abrasive according to claim 1, wherein the lanthanum dissolution inhibitor is contained in an amount of 0.01 to 0.9 parts by mass per 100 parts by mass of the mixed rare earth abrasive particles.
6. A polishing liquid comprising the cerium-based abrasive according to claim 1 and at least one selected from the group consisting of water and water-soluble organic solvents.
7. A method for producing the polishing liquid according to claim 6, comprising the steps of: The cerium-based abrasive; one or more selected from the group consisting of water and the water-soluble organic solvent; and (I) mixing the above to form a slurry.
8. A method for producing the polishing liquid according to claim 6, comprising the steps of: The cerium-based abrasive; The lanthanum dissolution inhibitor; one or more selected from the group consisting of water and the water-soluble organic solvent; and (II) mixing the above to form a slurry.
9. A method for producing the polishing liquid according to claim 6, comprising the steps of: The cerium-based abrasive; one or more selected from the group consisting of water and the water-soluble organic solvent; (III) mixing the above to form a slurry; The slurry obtained in the step (III) is A method for producing a polishing liquid, comprising: a step (IV) of adding and mixing the lanthanum dissolution inhibitor.
10. A method for polishing glass, comprising the step of carrying out polishing using the polishing liquid according to claim 6.
Citation Information
Patent Citations
Novel cerium abrasive composition and manufacture
JP1985035075A
Method for producing glass product
JP2012219006A
Cerium-based particle composition and its preparation
JP2012524129A
Abrasive material
WO2002031079A1
Cerium polishing agent and method for producing cerium polishing agent
WO2005042661A1